PENGARUH MOTIVASI DALAM PEMBELAJARAN SISWA UPAYA MENGATASI PERMASLAHAN BELAJAR - Marisa, Siti (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
Learning is a process of changing behavior from not knowing to knowing or from not being able to be able to. Because of that learning becomes something very important for one's life. In conducting learning activities, of course, requires a force called motivation. This paper tries to look further at how motivation influences one's learning activities. Literature approach is employed in this study to describe everything obtained to increase understanding related to motivation to learn. In general, motivation is divided into two, namely intrinsic and extrinsic. Problems that always cause difficulties for students to learn are internal factors that include cognitive, affective, and psychomotor domains, while external factors cover all situations and environmental conditions that do not support student learning activities. In addition, other factors that are more specifically causing difficulties for students in learning are dyslexia (inability to learn to read); dysgraphia (inability to learn or to write) and dyscalculia (inability to learn mathematics).